Fabrication of Normally Off AlGaN/GaN MOSFET Using a Self-Terminating Gate Recess Etching Technique - Xu, Zhe; Wang, Jinyan; Yang Liu; Cai, Jinbao; Liu, Jingqian; Wang, Maojun; Min Yu; Xie, Bing; Wu, Wengang; Ma, Xiaohua; Zhang, Jincheng (IEEE ELECTRON DEVICE LETTERS, 2013)
A self-terminating gate recess etching technique is first proposed to fabricate normally off AlGaN/GaN MOSFET. The gate recess process includes a thermal oxidation of the AlGaN barrier layer for 40 min at 615 degrees C followed by 45-min etching in potassium hydroxide solution at 70 degrees C, which is found to be self-terminated at the AlGaN/GaN interface with negligible effect on the underlying GaN layer, manifesting itself easy to control, highly repeatable, and promising for industrialization. The fabricated device based on this technique with atomic layer deposition Al2O3 as gate insulator exhibits a threshold voltage as high as 3.2 V with a maximum drain current over 200 mA/mm and a 60% increased breakdown voltage than that of the conventional high electron mobility transistors.